Susceptibility-Diffusion Mismatch Predicts Thrombolytic Outcomes: A Retrospective Cohort Study - Lou, M.; Chen, Z.; Wan, J.; Hu, H.; Cai, X.; Shi, Z.; Sun, J. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Asymmetric hypointensity of cerebral veins on susceptibility-weighted imaging has been shown to indirectly reflect tissue hypoxia after cerebral ischemia. We therefore investigated whether patients with prominent asymmetry of the cerebral veins on SWI and a relatively small diffusion-weighted imaging lesion (SWI-DWI mismatch), representing the presence of salvageable tissue, were more likely to benefit from thrombolytic therapy. MATERIALS AND METHODS: We conducted a retrospective study of the anterior circulation of patients with ischemic stroke with SWI/DWI acquired before thrombolysis. The asymmetry index was defined as the ratio of cerebral vein voxel count between the ischemic and normal hemisphere on the SWI phase map. We defined SWI-DWI mismatch as an asymmetry index score of ≥1.75 with a DWI lesion volume of ≤25 mL. Favorable outcome was defined as modified Rankin Scale 0–2 at 3 months. Univariate and multivariate logistic regression analyses were used to examine the association between the mismatch profile and favorable outcome. RESULTS: Fifty-four patients undergoing thrombolytic treatment were enrolled in this study. The rate of favorable outcome was significantly higher among patients with baseline SWI-DWI mismatch compared with those without (78% versus 44%; adjusted odds ratio, 6.317; 95% CI, 1.12–35.80; P = .037). Patients with SWI-DWI mismatch were also more likely to have a favorable outcome from reperfusion (91% versus 43%, P = .033) or recanalization (100% versus 40%, P = .013). The accuracy of SWI-DWI mismatch for predicting favorable outcome was higher than that of perfusion-diffusion mismatch (63% versus 48.1%). CONCLUSIONS: The presence of SWI-DWI mismatch may identify patients with ischemia who would benefit from early reperfusion therapy. AIasymmetry indexTIMIThrombolysis in Myocardial InfarctionTmaxtime-to-peak of the residue function